PENGARUH KEPATUHAN PAJAK TERHADAP PENINGKATAN OMZET UMKM TERKURASI DINAS KEBUDAYAAN DAN PARIWISATA KABUPATEN BOGOR - Evin Sofianti; Sriyani (Halu Oleo University, 2023)
This study aims to analyze the effect of compliance level and tax awareness of Micro, Small and Medium Enterprises (MSMEs) on increasing turnover. This study used quantitative methods. Primary data collection through questionnaires and structured interviews with 102 MSME owners. Data processing using Structural Equalling Modeling (SEM) and hypothesis testing using Smart PLS (Partial Least Square). The results of the research conducted have proven that there is a significant positive relationship between tax compliance, MSME awareness, and an increase in business turnover of curated actors of the Culture and Tourism Office in Bogor Regency in the last 5 years. Implications in efforts to extensify the business, good and regular tax report records are needed. Removing tax stigma reduces operating profits, but the reality is the opposite. The more compliant the tax obligations of a business entity, the better management has been applied in its business processes. This provides an increase in investor confidence to want to invest. This research has significance to provide a better understanding of the relationship between tax compliance, MSME awareness, and local economic growth. It is hoped that the results of this study can provide a foundation for the formulation of policies that support MSME tax compliance as a strategy to increase the contribution of this business sector to the country's economic development.